THE TOURIST’S ELEGY: I TERCULTURALITY I THE POETRY BY D. ZAWAWI IMRO E TITLE REFREI DI SUDUT DAM - Kurniawan, Abimardha (Kantor Bahasa Banten, 2015)
The annual literatur festival named Winternachten brought the fame Indonesian poet D.Zawawi Imron making contact with cultural things in the etherlands. He documented his culturalcontact through poems that collected in anthology Refrein di Sudut Dam (2003). By those poems wecan see how the intercultural communication had been. As subject of those poems, who represented by?Aku? within texts, the poet interpreted to make an assessment of the cultural practices whichfounded by him on the outside of his cultural locus. His interpretations act had influenced byIndonesian collective memories about Dutch colonization and also his identity construction asMoslem, Indonesian and Madura people. He also got any cultural shocks for his cultural contact. Theanticipation to its condition was the strategies of adaptation. But if those strategies were failing, hehad chosen to return to his mother-culture at all. He had many options to return because he just atourist who went to visit the foreign country.